Estudo da usinagem por torneamento de ligas de alumínio - Diógenes, Anderson Carmo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The non-ferrous materials have got so many mechanical, physical and chemical advantageous properties so that is provided to them consolidated position in industry. In this context, aluminium alloys have been seen a lot on many applications of engineering areas – specially on automotive, aeronautical and aerospace due to their main properties such as low density, high corrosion resistance, favorable structure weight / material resistance relation, among others characteristics that are mencioned through this study. This study aims to analyze the aluminium alloys behavior on a general context when they are used on turning process, taking for examples the 6262 and 7050 aluminium alloys. In this way, the analysis studies the datas obtained during the turning tests realized on 3 steps each one; those datas are concerning the medium and total rugosities – obtained with the assistance of a portable Surface Roughness Finish Tester, as well as the chips obtained during the tests - visual analysis, and the cutting tools wear – with the assistance of an optical microscope, under different conditions of application of cutting fluids (dry machining, application of coolant in abundance and MQL – Minimum Quantity of Lubricant). The results concerning this study show detailed information about influence of cutting fluids on the machining by turning of the aluminium alloys related on this work and also about aluminium alloys in general when they are used on turning processes with different conditions from one another. By this way, it was evident the MQL technique is the best one for the 6262 alloy. However, for 7050 alloy, it was evident that the dry machining is responsible for the best results

Os materiais não ferrosos possuem propriedades mecânicas, físicas e químicas que lhes propiciam posição consolidada no meio industrial. Neste contexto, encontramse as ligas de alumínio que têm sido muito reconhecidas em diversas áreas da engenharia – principalmente nos setores automobilístico, aeronáutico e aeroespacial, devido às suas principais características, tais como baixa densidade, elevada resistência à corrosão, relação peso da estrutura / resistência do material favorável, dentre outras mencionadas no corpo deste estudo. O estudo em questão visa analisar o comportamento de ligas de alumínio de forma geral quando submetidas ao processo de usinagem por torneamento, exemplificando para tanto, as ligas de alumínio 6262 e 7050. Com este objetivo, a análise feita busca estudar os dados obtidos durante os ensaios de torneamento realizado em 3 passes, no que tange às rugosidades média (Ra) e total (Ry) – com a utilização de um rugosímetro portátil , bem como aos cavacos formados – através de inspeção visual, sob condições de aplicação de fluido de corte diferentes (a seco, fluido abundante e MQF – Mínima Quantidade de Fluido). Os resultados deste trabalho oferecem informações detalhadas da influência dos fluidos de corte na usinagem das ligas de alumínio em questão e das ligas de alumínio de forma geral quando submetidas a diferentes condições de usinagem. Desta forma, ficou evidenciado para a liga 6262, como melhor condição de usinagem, de forma geral, a aplicação do fluido refrigerante mediante técnica MQF. Já no que diz respeito aos resultados obtidos com a liga 7050, constatou-se a usinagem a seco como responsável pelos melhores resultados
Keywords: Usinagem; Ligas de aluminio; Fluidos de corte; Resistencia de materiais; Aluminium; Cutting Fluid